The influence of information technology capability in sustainable competitive advantage of commercial banks in Nepal: organizational culture as mediating variable (Shaheed Smriti Journal, 2025)
The research aims to explore the impact of organizational information technology (IT) capability in measuring sustainable competitive advantage (SCA) in commercial banking industry in Nepal. The paper, based on the Resource-Based View (RBV) and the Model of Organizational Culture suggested by Schein, puts forward a set of hypotheses regarding a theoretical framework, in which IT capability (IT infrastructure and IT competence) reinforces SCA directly and indirectly via organizational culture as a mediational force. Descriptive research design has been used along with casual comparative research design. The data is collected using a questionnaire which is a seven-point Likert scale based questionnaire sent to survey 260 middle and senior managers of Nepal commercial banks. The results of the research indicate that IT knowledge significantly impacts the business culture and long-term competitive advantage and part of the relationship between IT capability and SCA is mediated by organizational culture, which is a key factor in maximizing IT investments. The research adds value to the literature, as it informs the business and IT alignment in an emerging economy as well as gives recommendations to the banking executives and policymakers, to develop regulatory frameworks that are conducive in stimulating IT-driven innovation within the banking industry to improve IT strategies towards long-term competitive advantage.